2016
DOI: 10.1016/j.bcp.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide mediated retinoic acid receptor signalling and inhibition of ceramide biosynthesis regulates adipogenesis, lipid accumulation, mitochondrial function and nutrient stress signalling in adipocytes and adipose tissue

Abstract: Graphical abstractProposed mechanistic action of FEN in adipocytes. RA inhibits adipogenesis through early RAR activation, which PPARγ agonist ROSI cannot prevent. FEN inhibits adipogenesis with a delayed response in RAR signalling, however, inhibition is lost when combined with ROSI. The 4-OXO FEN catabolite cannot inhibit adipogenesis through RAR activation, but like FEN’s RAR-independent effects, displays increased phosphorylation of Akt, mild cellular stress/autophagy induction and decreased lipid accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…We and others have already shown that FEN can inhibit the final step in ceramide synthesis through blockade of the enzyme dihydroceramide desaturase 1 in adipose tissue2022. Here, we have now shown that ceramide synthesis is also blocked by FEN in liver in a genetic model of severe obesity and insulin resistance.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We and others have already shown that FEN can inhibit the final step in ceramide synthesis through blockade of the enzyme dihydroceramide desaturase 1 in adipose tissue2022. Here, we have now shown that ceramide synthesis is also blocked by FEN in liver in a genetic model of severe obesity and insulin resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Previous work has shown that FEN treatment results in alterations in ceramide and dihydroceramide levels in HFD obese mice, in association with improvements in glucose homeostasis and insulin sensitivity2022. To determine whether FEN could have the same effect in genetically-obese mice, lipid analysis was performed in liver tissue from Lepr db mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, in the present study fenretinide treatment was found to reduce body weight gain and fat mass in both EKO and wild‐type mice. This mainly occurs via the inhibition of adipogenesis through prevention of C/EBPβ transcription (Mcilroy et al, ). The treatment was not expected to alter the food intake (Shearer et al, ) and, indeed, food intake was unchanged in EKO and negligibly increased in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, Mcilroy et al showed that fenretinide-mediated retinoic acid receptor signaling and inhibition of ceramide biosynthesis regulates adipogenesis, lipid accumulation, mitochondrial function, and nutrient stress signaling in adipocytes and adipose tissue. Their findings suggested that fenretinide utilizes retinoid-acid-receptor (RAR)-dependent and independent pathways to regulate cell biology that could be relevant to the current results [8].…”
mentioning
confidence: 78%